Duality for a class of second order symmetric nondifferentiable fractional variational problems - Prasad, A.K.; Singh, A.P.; Khatri, S. (Faculty of Organizational Sciences, Belgrade, 2020)
The present work frames a pair of symmetric dual problems for second order nondifferentiable fractional variational problems over cone constraints with the help of support functions. Weak, strong and converse duality theorems are derived under second order F-convexity assumptions. By removing time dependency, static case of the problem is obtained. Suitable numerical example is constructed. © 2020 Faculty of Organizational Sciences, Belgrade. All rights reserved.
Keywords: Nondifferentiable Programming; Second Order F-convexity; Symmetric Duality; Variational Problem